Ratooning increases production of sweetpotato seed vines multiplied in insect-proof net tunnels in Tanzania - Ogero, K.; Okuku, H.S.; McEwan, M.; Almekinders, Conny J.M.; Kreuze, Jan F.; Struik, P.C.; Vlugt, R. van der. (Cambridge University Press, 2023)
Insect-proof net tunnels can help reduce virus infection of clean virus-tested sweetpotato seed produced by decentralized seed producers. However, optimal management is required to maintain both quality and quantity of seed produced. This study investigated the effect of the ratoon cropping technique on vine production in net tunnels and open fields. Virus-tested planting material of two varieties, Kabode and Mataya, were grown in net tunnels and open fields. Each variety had 80 plants per plot, with 40 following the ratooning technique and 40 a replanting technique. The ratooned crop was harvested six times, comprising the initial harvest and five regrowths. This covered 14 months representing six generations of vine production. The number of vines, number of nodes per vine, and vine length were recorded. The number of plants showing virus symptoms was also recorded. The ratoon cropping technique produced more vines compared with the replanting technique in both net tunnels and open fields. Cv. Kabode produced more vines in open fields compared with net tunnels regardless of cropping technique. On the other hand, cv. Mataya produced relatively equal numbers of vines in net tunnels and open fields. Despite ratooning leading to more vine production compared with replanting, the technique led to higher virus incidences on plants grown in the open. This also varied with variety with the highest virus disease incidences being recorded on cv. Mataya. We recommend the ratoon cropping technique for sweetpotato vine production in net tunnels. Replanting technique should be adopted for vine production in the open fields because it acts as a key control strategy for virus infections even for susceptible varieties.